2003
DOI: 10.1128/mcb.23.20.7315-7328.2003
|View full text |Cite
|
Sign up to set email alerts
|

Akt-Directed Glucose Metabolism Can Prevent Bax Conformation Change and Promote Growth Factor-Independent Survival

Abstract: The serine/threonine kinase Akt is a component of many receptor signal transduction pathways and can prevent cell death following growth factor withdrawal. Here, we show that Akt inhibition of cell death is not dependent on new protein translation. Instead, Akt inhibition of cell death requires glucose hydrolysis through glycolysis. Akt was found to regulate multiple steps in glycolysis via posttranscriptional mechanisms that included localization of the glucose transporter, Glut1, to the cell surface and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
439
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 514 publications
(462 citation statements)
references
References 66 publications
19
439
0
4
Order By: Relevance
“…These increases were less but of the same order of magnitude as those reported for MyrAkt. 35 Whereas mitochondrial HK activity appears to be independent of IL-3 in T cells expressing MyrAkt, 42 CSF-1 treatment had an additional and substantial effect, consistent with the finding that CSF-1 further stimulated Akt activity in DKI/p110* and DKI/E40K cells ( Figure 3e). …”
Section: The Role Of Hk In Csf-1-mediated Mitogenic Signalingsupporting
confidence: 79%
See 1 more Smart Citation
“…These increases were less but of the same order of magnitude as those reported for MyrAkt. 35 Whereas mitochondrial HK activity appears to be independent of IL-3 in T cells expressing MyrAkt, 42 CSF-1 treatment had an additional and substantial effect, consistent with the finding that CSF-1 further stimulated Akt activity in DKI/p110* and DKI/E40K cells ( Figure 3e). …”
Section: The Role Of Hk In Csf-1-mediated Mitogenic Signalingsupporting
confidence: 79%
“…Previous studies showed that enforced overexpression of MyrAkt in B cells was completely protective against cell death induced by IL-3 withdrawl and that this was dependent on glucose availability. 42 When a signaling pathway is dysregulated, such as from chronic Akt activation owing to MyrAkt overexpression, cells can become addicted to the growth/ survival effects conferred by the pathway and exhibit hypersensitivity to inhibition of that pathway. Our results extend the observations made with MyrAkt to more physiologic situations such as the DKI receptor where growth factor signaling and feedback mechanisms remain largely intact.…”
Section: Discussionmentioning
confidence: 99%
“…A few examples are cited as follows: oncogenic Ras or activation of the PI3K/Akt pathway promotes glycolysis. Akt stimulates membrane localization of glucose transporters and enhances transcription or activity of glycolytic enzymes such as hexokinase and phosphofructokinase (Gottlob et al, 2001;Rathmell et al, 2003). K-Ras promotes transcription of several glycolytic enzymes (Chiaradonna et al, 2006).…”
Section: Metabolic Transformation: Cancer's Friend and Foementioning
confidence: 99%
“…They demonstrated that by increasing glucose uptake through Glut1 overexpression in hematopoietic cells, they could efficiently delay apoptosis induced by interleukin-3 withdrawal. In addition, it was shown that glucose uptake and phosphorylation are required by constitutively active Akt to protect from interleukin-3 withdrawal (Rathmell et al, 2003). The process of deciphering the mechanism behind it has begun.…”
Section: Glycolysis Protects From Deprivation Of Growth Factorsmentioning
confidence: 99%
“…Multiple biological processes, such as cell proliferation, cell metabolism and cell survival, are all regulated by Akt 10. The PI3K/Akt signal pathway mediates cell survival by promoting aerobic glycolysis 11. Most of the cancer cells produce abundant lactate to supply energy, but it is inefficient to generate ATP.…”
Section: Introductionmentioning
confidence: 99%